EFFECT OF PHYTASE SUPPLEMENTATION IN SOYBEAN MEAL BASED DIET ON NUTRIENT DIGESTIBILITY AND GROWTH PERFORMANCE OF GREEN CATFISH (Hemibagrus nemurus) - DEDI JUSADI; YULISMAN; ING MOKOGINTA (SEAMEO BIOTROP, 2008)
This experiment was conducted to evaluate the effect of phytase supplemented to the diet on phosphorus (P) digestibility and growth performance of the green catfish Hemibagrus nemurus. Five kinds of experimental diets were used in this experiment, namely diets A, B, C, D and E. Diet A, as a control, was supplemented with inorganic P, without phytase supplementation. Diet B, C, D and E were supplemented with 0, 20, 40 and 60 mg phytase/100 g soybean meal (SBM), respectively, without inorganic P supplementation. Fifteen fish with initial body weight of 6.9 + 0.2 g were stocked into each 60-l aquarium. Fish were fed on the diets for 60 days. Results indicated that P digestibility increased from 64.5% to 87.0% as phytase supplement increased from 0 mg in diet B to 60 mg phytase/100 g SBM in diet E. P digestibility in diet E was higher than that in diet A (77.6%). The daily growth rate and feed conversion ratio followed similar trend. P, Calcium (Ca) and Zinc (Zn) concentration in the whole body and bone of fish fed diet E were higher than the fish fed diet B, C and D, but were insignificant compared to the fish fed diet A. Nitrogen (N) and P loading by fish fed diet E were, respectively, 76% and 20% lower than those in fish fed the control diet. It is concluded that the inclusion of 60 mg phytase/100 g SBM in the diet of the green catfish could replace the utilization of inorganic P increase the digestibility of the diet thereby resulting in increased growth rate and reduced excretion of P and N into the waters. Keywords: Hemibagrus nemurus, phytase, soybean meal, phosphorus.